Prokineticin 1–prokineticin receptor 1 signaling promotes angiogenesis in the porcine endometrium during pregnancy. Issue 3 (30th April 2020) - Goryszewska, Ewelina; Kaczynski, Piotr; Balboni, Gianfranco; Waclawik, Agnieszka
Abstract: Pregnancy establishment in mammals, including pigs, requires proper communication between embryos and the maternal reproductive tract. Prokineticin 1 (PROK1) has been described as a secretory protein with pleiotropic functions and as a novel tissue-specific angiogenic factor. However, despite the studies performed mainly on human cell lines and in mice, the function of PROK1 in the endometrium during early pregnancy is still not fully elucidated. We hypothesized that PROK1 contributes to pregnancy establishment in pigs. The present study is the first to report that the expression of PROK1 and its receptor (PROKR1) is elevated in the porcine endometrium during the implantation and early placentation period. PROK1 protein was detected mainly in luminal epithelial cells, glandular epithelial cells, and blood vessels in the endometrium. Using the porcine in vivo model of unilateral pregnancy, we revealed that conceptuses induced the endometrial expression of PROK1 and PROKR1. Moreover, the embryonic signal, estradiol-17β, as well as progesterone, stimulated the endometrial expression of PROK1 and PROKR1. We also evidenced that PROK1–PROKR1 signaling supports endometrial angiogenesis in pigs. The PROK1-stimulated proliferation of primary porcine endometrial endothelial (PEE) cells involved PI3K/AKT/mTOR, MAPK, cAMP, and NFKB signaling pathways. Furthermore, PROK1 via PROKR1 promoted the formation of capillary-like structures by PEE cells. PROK1 also stimulated VEGFA and PGF2α secretion, which in turn may indirectly support angiogenic changes within endometrial tissue. In summary, our study suggests that PROK1 acts as an embryonic signal mediator that regulates endometrial angiogenesis and secretory function during the implantation and early placentation period in pigs. Abstract : Prokineticin 1 is an embryonic signal mediator that, acting through PROKR1, promotes angiogenesis in the porcine endometrium during the implantation and early placentation period.